Forest Products Biotechnology - Bruce, Alan;Ed. Palfreyman, John W;Ed (Taylor & Francis, 1998)
This text presents a review of specialist research directed towards efficient and environmentally sensitive use of forests. An introductory chapter explains the structure and anatomy of wood.